Assessing fire frequency and structural fire behaviour of England statistics according to BS PD 7974-7. (March 2021) - Manes, Martina; Rush, David
Abstract: Contemporary structural fire statistics are fundamental in engineering design practice to evaluate likelihood and consequence of fire for different property types, and to investigate how different safety measures impact fire spread. British Standard PD 7974-7:2003 has recently been updated using USA fire statistics; this paper compares PD 7974-7:2003 to current England statistics (named UK statistics) using one public and one Home Office dataset. PD 7974-7:2003 overestimates fire frequency with values up to 5 times greater than the ones found in UK and USA. When fire frequency is plotted against total floor space, for different property types, power laws with positive or negative exponent and polynomial functions provide better approximations of the data than the current codes. Average area damage from PD 7974-7:2003 has been compared to fire and total damage from UK datasets where fire size is usually well confined to room of origin at 20% of fires based on the publicly available dataset. When fires exceeding specific areas of damage are considered, PD 7974-7:2003 usually overestimates fire damage and underestimates total damage, with more damage evident when sprinklers are absent compared to when they are present.